PENGARUH LAYANAN CALL CENTER WANAARTHA LIFE JAKARTA TERHADAP KEPUASAN NASABAH WAL INVEST DALAM MEMPEROLEH INFORMASI - Giovani Shaddela (Jurnal Visi Komunikasi, 2017)
Service are things that imply a relationship between two parties, which is the party that provides service and the party who gets or needs theservice. As a service provider, an organization or company must be able to provide something that can please the customers. Therefore, the call center is built as a bridge or connector to create customer satisfaction. This research was conducted todetermine how the call center service has influenced the customer satisfaction wal invest wanaartha life. The independent variable in this study is call center service (X), and the dependent variable is customer satisfaction (Y). This study uses a quantitative approach with comparative causal types. The method used is a survey by distributing questionnaires. The sampling technique of the total population is 225 wal invest customers, obtained as many as 144 samples with the Taro Yamane formula. The technique used in this study is simple random sampling. To see how many samples will be used, the sampling formula that being used is Taro Yamane. The results showed that the influence off call center services on customer satisfaction wal investana life 99.7%, and the remaining 0.3% were influenced by other factors